Eye Diseases - Recent Advances, New Perspectives and Therapeutic Options 2023
DOI: 10.5772/intechopen.108077
|View full text |Cite
|
Sign up to set email alerts
|

Optic Coherence Tomography Angiography in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is a progressive microvascular disease considerer as the most important cause of acquired vision loss in the world. OCT angiography (OCT-A) has drastically improved the diagnosis and follow-up of DR showing alterations before changes in the fundus will be visible. With OCT-A, it is possible to quantify several parameters such as the macular vascular density (MVD) and foveal avascular zone (FAZ). This new technique will be important for early detection, follow- up, and monitoring treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…OCTA can non-invasively reveal the structures of multiple layers of the vascular plexus, including the superficial capillary plexus (SCP), intermediate capillary plexus, deep capillary plexus (DCP), and peripapillary radial plexus (PRP) ( 32 , 33 ). Some previous studies reported that the DCP was more susceptible to ischemia and significantly related to the progression of DR than the SCP ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…OCTA can non-invasively reveal the structures of multiple layers of the vascular plexus, including the superficial capillary plexus (SCP), intermediate capillary plexus, deep capillary plexus (DCP), and peripapillary radial plexus (PRP) ( 32 , 33 ). Some previous studies reported that the DCP was more susceptible to ischemia and significantly related to the progression of DR than the SCP ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that aspect, images were given as input through 101 layers of residual blocks in the proposed ResNet101 model by Ryu et al, in which the input and output feature maps from the convolution layers were repeatedly added. 78,84 The design layout of the ResNet101 framework for identifying early indicators of DR and its classification is illustrated in Figure 9. To find DR, an end-to-end categorization task was carried out.…”
Section: Impact Of Ai To Diagnose Dr From Octa Imagementioning
confidence: 99%